2022
DOI: 10.3390/ma15113830
|View full text |Cite
|
Sign up to set email alerts
|

Hinged Adaptive Fiber-Rubber Composites Driven by Shape Memory Alloys—Development and Simulation

Abstract: Adaptive structures based on fiber-rubber composites with integrated Shape Memory Alloys are promising candidates for active deformation tasks in the fields of soft robotics and human-machine interactions. Solid-body hinges improve the deformation behavior of such composite structures. Textile technology enables the user to develop reinforcement fabrics with tailored properties suited for hinged actuation mechanisms. In this work, flat knitting technology is used to create biaxially reinforced, multilayer knit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The glass fibres (GFs) used in this work have a fineness of 272 Tex and were assigned to an orthotropic elastic material model with the elastic modulus in the main fibre direction, and the second and third directions were defined for numerical stability. The model parameters used for this work are considered from the previous works in the line of project from Lohse et al [ 41 , 46 ] and are shown in Table 1 and Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The glass fibres (GFs) used in this work have a fineness of 272 Tex and were assigned to an orthotropic elastic material model with the elastic modulus in the main fibre direction, and the second and third directions were defined for numerical stability. The model parameters used for this work are considered from the previous works in the line of project from Lohse et al [ 41 , 46 ] and are shown in Table 1 and Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…One approach to creating soft structures is the integration of textile actuators based on SMAs into fiber-reinforced elastomer composites [9,10]. Fiber-reinforced polymers (FRPs) provide design freedom, allowing tailored combinations of matrix and reinforcement fibers for specific applications.…”
Section: Introductionmentioning
confidence: 99%
“…Lohse et al [8] developed a novel type of actively deformable composites by knitting SMA Zhenbi Wang, Achyuth R. Annadata, Anja Winkler, Rainer Barth, Anett Endesfelder, Chokri Cherif, Martina Zimmermann, Niels Modler wires into glass fiber fabrics and impregnating them with liquid silicone rubber. By adjusting the knitting pattern, they were able to modify the stiffness of the composite material [13]. Driven by SMA wires, the material structure with flexible middle section and stiff sides can achieve a jointlike motion [13].…”
Section: Introductionmentioning
confidence: 99%
“…By adjusting the knitting pattern, they were able to modify the stiffness of the composite material [13]. Driven by SMA wires, the material structure with flexible middle section and stiff sides can achieve a jointlike motion [13]. Mersch et al [14] overbraided the SMA wire with copper wires and polyamide yarns, which formed a core-sheath structure, and sewed it onto a glass fiber woven in a U-shaped pattern using a tailored fiber placement (TFP) machine, and finally impregnated the textile with silicone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation